The Meaning of the Explicit and Inexplicit Approaches in Wŏnhyo's System of the Two Hindrances (Ijang ŭi 二障義) - Muller, A. Charles (Journal of Korean religions, 2017)
Wŏnhyo's Ijang ŭi is a lengthy treatise that examines and explains the afflictive and cognitive hindrances to liberation and enlightenment more thoroughly than any known work in the history of Buddhism. While this in itself is sufficient to make it a watershed work, the treatise goes even further, in defining two distinctive systems of the hindrances, which are associated with the two major doctrinal lineages of Yogâcāra and Tathāgatagarbha. These two systems are labeled by Wŏnhyo with the Buddhist exegetical terms "explicit" (Qnītârtha, 顯了門) and "inexplicit" (Qneyârtha, 隱密門). These, I argue, are for Wŏnhyo not value-laden terms as usually seen in East Asian doctrinal classification systems, but conceived based on Wŏnhyo's impression of the relative clarity (or lack thereof) of their systematic descriptions in the source texts of the two traditions. In the end, Wŏnhyo shows not only how these systems differ, but how they also mutually complement and inform each other. This makes this treatise an emblematic work demonstrating the Silla scholiast's hallmark methodological approach of doctrinal synthesis (hwajaeng). Wŏnhyo's work on this topic deeply influenced scholarship on the hindrances by later Faxiang, Tiantai, and Huayan scholars in China, Korea, and Japan. In the course of introducing the Ijang ŭi, I also provide a brief outline of the development of the two hindrances concepts in the Tathāgatagarbha and Yogâcāra traditions, along with a synopsis of the major pre-Wŏnhyo treatise on the hindrances, that by the Chinese scholar Huiyuan.